Increase in dNTP pool size during the DNA damage response plays a key role in spontaneous and induced-mutagenesis in Escherichia coli - Gon, Stéphanie; Napolitano, Rita; Rocha, Walter; Coulon, Stéphane; Fuchs, Robert P (Proceedings of the National Academy of Sciences - PNAS, 2011)
Exposure of Escherichia coli to UV light increases expression of NrdAB, the major ribonucleotide reductase leading to a moderate increase in dNTP levels. The role of elevated dNTP levels during translesion synthesis (TLS) across specific replication-blocking lesions was investigated. Here we show that although the specialized DNA polymerase PolV is necessary for replication across UV-lesions, such as cyclobutane pyrimidine dimers or pyrimidine(6-4)pyrimidone photoproduct, Pol V per se is not sufficient. Indeed, efficient TLS additionally requires elevated dNTP levels. Similarly, for the bypass of an N-2-acetylaminofluorene-guanine adduct that requires Pol II instead of PolV, efficient TLS is only observed under conditions of high dNTP levels. We suggest that increased dNTP levels transiently modify the activity balance of Pol III (i.e., increasing the polymerase and reducing the proofreading functions). Indeed, we show that the stimulation of TLS by elevated dNTP levels can be mimicked by genetic inactivation of the proofreading function (mutD5 allele). We also show that spontaneous mutagenesis increases proportionally to dNTP pool levels, thus defining a unique spontaneous mutator phenotype. The so-called "dNTP mutator" phenotype does not depend upon any of the specialized DNA polymerases, and is thus likely to reflect an increase in Pol III's own replication errors because of the modified activity balance of Pol III. As up-regulation of the dNTP pool size represents a common physiological response to DNA damage, the present model is likely to represent a general and unique paradigm for TLS pathways in many organisms.